Secondhand Smoke in the Workplace Is Associated With Depression in Korean Workers - Kim, Seunghan; Oh, Juyeon; Yun, Byungyoon; Cho, Ara; Sim, Juho; Yoon, Jin-Ha (Frontiers in Public Health, 2022)
Background Smoking negatively affects health, and previous studies argue that secondhand smoke (SHS) has a significantly negative health effect. We investigated whether SHS in the workplace influences workers' depression. Methods Three years of data (2014, 2016, and 2018) from the Korean National Health and Nutrition Examination Survey were analyzed. Participants who were not current smokers were classified into the occupational SHS exposed and non-exposed groups. Multivariate logistic regression was performed to estimate odds ratios (ORs) and 95% confidence intervals (CIs) by adjusting various covariates. Stratified analysis with variables, such as year, sex, occupational classification, average working hours, was additionally performed. Results The crude ORs of depression was 1.51 (95% CI: 1.27-1.80), and the fully adjusted OR with all the covariates was 1.57 (95% CI:1.30-1.88). This indicated a significant relationship between occupational SHS and depression. The ORs increased every 2 years: 1.07 (95% CI:0.79-1.44) in 2014, 1.88 (95% CI:1.34-2.64) in 2016, and 2.07 (95% CI:1.43-2.99) in year 2018. Stratification analysis also showed a significant association between SHS and depression among those in the prolonged work hours group and male employees, as well as blue and white collar workers. Limitations This study is a cross-sectional study of an homogenous population; therefore, the temporal relationship between exposure to SHS and depression is uncertain. Furthermore, recall and response bias might occur due to using self-reported questionnaires. Conclusion SHS in the workplace was significantly associated with workers’ depression. Our study provides insights into the impact of exposure to SHS for workers and provides a basis for further research and policy-making in this field.